THE CONTRIBUTION OF THE HOUSEHOLD MEMBERS TO FISHERMAN HOUSEHOLD INCOME IN KUALA MERBAU VILLAGE MERBAU ISLAND DISTRICTS KEPULAUAN MERANTI REGENCY RIAU PROVINCE - Hamid, Hamdi; ', Irmalina; ', Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was implemented on February 2016, in Kuala Merbau Village Merbau Island Districts Kepulauan Meranti Regency Riau Province. The purpose of the research are to identify the types of activities of fisherman household members, to analyze the contribution of fisherman household. Members to help increase household income and to know the reason of fisherman household members to work. The methods was used by survey method and the determination of respondents with census. The results of this research indicate that activities performed by fisherman household members in Kuala Merbau Village on the fisheries sector and non fisheries. The contribution of fisherman household members are relatively high contribution of the husband 74,5%, the wife contribution 11,2% is low and contribution of childrens 14,3% is low. The reasons of fisherman’s wife to participate in work up namely are to increase revenue, to finding children's education and use full the time for advantage. The reasons of children to work are to help the household economy and meet their own needs.Keywords : Contribution, Fisherman Household Members, Income.